Impaired Limb Functional Outcome of Peripheral Nerve Regeneration Is Marked by Incomplete Recovery of Paw Muscle Atrophy and Brain Functional Connectivity in a Rat Forearm Nerve Repair Model - Qiyuan Bao; Qi Liu; Jun Wang; Yuhui Shen; Weibin Zhang (Neural Plasticity)
Skilled sensorimotor deficit is an unsolved problem of peripheral nerve injury (PNI) led by limb trauma or malignancies, despite the improvements in surgical techniques of peripheral nerve anastomosis. It is now accepted that successful functional recovery of PNI relies tremendously on the multilevel neural plasticity from the muscle to the brain. However, animal models that recapitulate these processes are still lacking. In this report, we developed a rat model of PNI to longitudinally assess peripheral muscle reinnervation and brain functional reorganization using noninvasive imaging technology. Based on such model, we compared the longitudinal changes of the rat forepaw intrinsic muscle volume and the seed-based functional connectivity of the sensorimotor cortex after nerve repair. We found that the improvement of skilled limb function and the recovery of paw intrinsic muscle following nerve regeneration are incomplete, which correlated with the functional connectivity between the primary motor cortex and dorsal striatum. Our results were highly relevant to the clinical observations and provided a framework for future investigations that aim to study the peripheral central sensorimotor circuitry underlying skilled limb function recovery after PNI.